If The World Were Without Religion, Would There Still Be Conflict Among Us? (A Philosophical Investigation Into The Relationship Between Religion And Conflict) - Al-Razi, Muhammad Fakhruddin (AL-ADYAN, 2025)
Religion and conflict are two things that have long appeared in human life. The inevitability between both cannot be separated. But in the next step, many parties then positioned religion as the source of the emergence of major conflicts in human civilization. A number of conflicts with religious nuances have made a number of parties' views even more cynical about religion. There were even some scholars who presupposed the absence of religion on earth so that painful conflicts in history would never occur. Through the results of an investigation of literature studies, this article tries to answer how the relationship between the two is in human life. Answering questions about does religion really create conflict? What if religion doesn't exist, will bloody conflicts still occur? The results of the study show that the presence or absence of religion has nothing to do with the presence or absence of conflict in human life. Even though religion can give birth to conflict, on the other hand religion also plays a role as a conflict mediator. Even the absence of religion does not guarantee that humans will never have conflicts. That way, the key is to strengthen awareness of tolerance among religious communities so that human life can become more harmonious and even though conflicts cannot be avoided, through the awareness of tolerance conflicts can be resolved peacefully and wisely.